Examining Ja'farī Jurisprudence: The Incorporation of the Leonine Clause in Partnership and Company Contracts - Heshmatollah Samavati (Turkish Journal of Shiite Studies)
The Leonine clause, a topic relatively underexplored, holds substantial importance within the context of partnership and company contracts. This research aims to analyze this clause through the lens of Ja'farī jurisprudence, shedding light on the diverse perspectives presented by Shia jurists. To achieve this goal, a series of preliminary discussions were initiated. Initially, the discourse delved into defining the Leonine clause and its legal status across various jurisdictions. Subsequently, we explored the concept of contractual partnerships, the requirements of partnership contracts, and the classification of conditions in Islamic law, distinguishing between valid, invalid, and nullifying conditions. Our primary focus revolved around the Leonine clause within partnership contracts as interpreted through Ja'farī jurisprudence. We elucidated the contrasting viewpoints expressed by Shia jurists regarding this specific condition. Furthermore, we analyzed the placement of the Leonine clause in contemporary company contracts, considering its validity and consequential impact on such agreements. Ultimately, drawing from the perspectives of both early and contemporary Shia jurists, we argued for the invalidity of the Leonine clause and its nullifying effect on company contracts.